Mobile Game-Based Learning (mGBL): Application Development and Heuristics Evaluation Strategy - Syamsul Bahrin Zaibon; Norshuhada Shiratuddin (Malaysian Journal of Learning and Instruction, 2010)
Purpose â€“ This article presents an approach to developing a mobile game-based learning (mGBL) application by adapting unified characteristics of learning theories and approaches. In addition, the study also identified the strategy to evaluate mGBL.